Length-weight and morphometric analysis of mud lobster, Thalassina anomala from Sarawak, Malaysia - Zakaria, Nur Nadiah; Malahubban, Masnindah; Fakurazi, Sharida; Wong, Sie Chuong; Rajaee, Amy Halimah (Universiti Putra Malaysia Press, 2019)
Mud lobsters (Thalassina spp.) are nocturnal organisms, belong to Order Decapoda which are lesser known and least studied although their presence were widely distributed across the Indo-West Pacific Region. Mud lobster is considered as an important organism in the mangrove ecosystem for its burrowing activities and the role of its mounds or burrows as home to other animals. All mud lobster samples collected from four distinct regions in Sarawak (Kuala Tatau, Kuala Balingian, Sarikei and Lingga) were identified as Thalassina anomala based on the morphological characteristics. Morphometric variations between sexes of T. anomala were examined. Sexual dimorphism can be observed where males had significantly longer carapace length, left chelae propodus length and larger left chelae propodus width compared to females (p<0.05). Meanwhile, sexual dimorphism can also be seen in the abdominal width, in which it was significantly larger in females, for both absolute values (p<0.01) and also the relative values (p<0.001). The length-weight relationship of T. anomala were analysed between sexes by regression analysis. Results showed that males had isometric growth rate for carapace length-weight (CL/W), total length-weight (TL/W) and abdominal length-weight (ABL/W) relationships. However, females had negative allometric growth in CL/W and ABL/W relationship and isometric growth in TL/W relationship. Data from this study is able to provide baseline information which are useful for future reference on mud lobster resource management in Sarawak, Malaysia.